تحسين محددات المحركات التحريضية باستخدام التعويض التسلسلي (الطولاني) للاستطاعة الردية. - حسن, عزت (Latakia University Journal -Engineering Sciences Series, 2019)
تناول البحث علاقة الاستطاعة الردية التي يستهلكها المحرك التحريضي مع جهد التغذية؛ إذ بيَّن مقدار التغير وسببه في استهلاك هذه الاستطاعة مع تزايد جهد التغذية أو تناقصه، ومع ثبات قيمة الحمولة المطبقة على محور المحرك أو تغيره وبالتالي تم إيجاد العلاقة بين معامل الاستطاعة الردية وجهد التغذية عند حمولات مختلفة ومقارنة النتائج. ونتيجة للتأثيرات السلبية للاستطاعة الردية في محددات المحرك فقد عالج البحث كيفية تحسين محددات المحرك عن طريق استخدام التعويض التسلسلي للاستطاعة الردية؛ إذ يمكن باستخدام طريقة التعويض المذكورة زيادة معامل الحمولة وعزم إقلاع المحرك من دون التغيير في قيمة الاستطاعة الاسمية أو في وزن المحرك وحجمه, أو يمكن بالعكس تخفيض وزن المحرك وحجمه عند عزم الإقلاع نفسه ومعامل الحمولة وتعدّ النتيجة إيجابية في كلتا الحالتين. This research has dealt with the link between the reactive power of the induction motor consumption and power supply. It has also shown that the amount and cause of power consumption vary, according to rise and drop in power supply as well as the constancy and variability of the applied load on the motor axis. This helps us find the relation between the reactive power factor (tgφ) and the power supply of different load-values. Then, the results are analyzed. Due to the negative reactive power effects on the motor parameters, the current research has also analyzed how to improve motor parameters, using the successive (longitudinal) reactive power. This will help us increase the loading factor, the motor momentum start-up, without change in the nominal power values or the motor volume and weight. Conversely, the motor-weight and volume of the same load factor and starting-up momentum can be reduced. The obtained results are positive in both cases.